Pengaruh Tingkat Pendidikan Terhadap Kinerja Perangkat Desa Bunga Jadi Kecamatan Muara Kaman - Muhson Danny Setyawan; Joko Sabtohadi; Hedi Suhartono (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2022)
Abstract:The purpose of this research is to know the device profile flower village So subdistrict of Muara Kaman Kutai Kartanegara Regency and to know the influence of educational level on performance of devices flower village So Sub Muara Kaman District Kukar.The value t calculate amounted to 5.51 while theoretical value t with the degrees of freedom (the degree of the freedom) to the respondents amounted to 46 with the calculation rules (n-2/46-2 = 44) at the 5% level (α = 0.05) is 1.680230 or 1.68 1.68 > 5.51 meaning. Thus the hypothesis put forward, namely: that the level of education affects the performance of the device so the flower village sub district of Kutai Kartanegara Regency Muara Kaman is acceptable because it has been proven to be true.Keywords: Level Of Education, The Performance Of The Device Of The Village